Gender Distinctions of Personality Self-Realization in Chinese Students - - Chzhan Pan Hao; - Chzhan Ten (Peoples' Friendship University of Russia (RUDN University), 2013)
The structural characteristics of personality self-realization of the Chinese students are analyzed in the article. The hierarchical structure of the expressiveness of the certain variables of the above mentioned phenomenon is examined. On the basis of the factorial analysis the substantial analysis of the self-realization gender distinctions is given.